OPEN SOURCE SOFTWARE FOR THE DEVELOPMENT OF INFORMATIONAL SYSTEMS: COMPARATIVE ANALYSUS AND DEVELOPMENT PROSPECTS IN UKRAINE - Boiko, Ivan; Lupenko, Sergiy; Luckiv, Andriy (International Journal of Computing, 2014)
In the article possibilities of opened software for information systems development and its perspectives in Ukraine are analyzed; the aspects of software development, using and cooperation are considered; the main problems which arise at software development and ways of their decision are resulted; the question of legal software using in work of researcher is reflected.